An approach for managing the evolution of web-based educational applications. (12th May 2004) - Psaromiligkos, Yannis; Retalis, Symeon
The management of the infrastructure and content of the World Wide Web is a growing problem for the development of web-based educational applications (WbEA) and is hidden beneath the tremendous benefits of the web. Moreover, such systems undergo more frequent and quite extensive changes in their development and operational period because the client's perception (either the learner, the teacher or institutional organisation) of the complete end product is a "moving target". So, there is a need for a disciplined approach to managing the evolution of web-based educational applications. Such a disciplined approach as applied throughout the software engineering process is called software configuration management (SCM). This paper begins a discussion of how the development of web-based educational applications could benefit from SCM techniques and tools and proposes a model for the management of the evolution of such systems. The model couples the development and evolution process of WbEA configurations into one framework, which seems promising for the implementation of a configuration management process. Also, the model focuses on the development of the web-based educational content, defining the configurations of the items involved in the underlying process. Finally, an example is given to demonstrate the benefits of the use of this approach.